Strengthening screening for infectious diseases and vaccination among migrants in Europe: What is needed to close the implementation gaps?. Issue 39 (January 2021) - Noori, Teymur; Hargreaves, Sally; Greenaway, Christina; van der Werf, Marieke; Driedger, Matt; Morton, Rachael L.; Hui, Charles; Requena-Mendez, Ana; Agbata, Eric; Myran, Daniel T.; Pareek, Manish; Campos-Matos, Ines; et al.
Abstract: Migration to the European Union (EU)/European Economic Area (EEA) affects the epidemiology of infectious diseases, including tuberculosis (TB), HIV, hepatitis B/C, and parasitic diseases. Some sub-populations of migrants are also considered to be an under-immunised group and thus at risk of vaccine-preventable diseases. Providing high-risk migrants access to timely and efficacious screening and vaccination, and understanding how best to implement more integrated screening and vaccination programmes into European health systems ensuring linkage to care and treatment, is key to improving the health of migrants and their communities, alongside meeting national and regional targets for infection surveillance, control, and elimination. The European Centre for Disease Prevention and Control (ECDC) has responded to calls to action to improve migrant health and strengthen universal health coverage by developing evidence-based guidance for policy makers, public health experts, and front-line healthcare professionals on how to approach screening and vaccination in newly arrived migrants within the EU/EEA. In this Commentary, we provide a perspective towards developing efficacious screening and vaccination of newly arrived migrants, with a focus on defining implementation challenges and evidence gaps in high-migrant receiving EU/EEA countries. There is a need now to leverage the increasing momentum around migrant health to both strengthen the evidence-base and to advocate for universal access to health care for all migrants in the EU/EEA, including undocumented migrants. This should include voluntary, confidential, and non-stigmatising screening and vaccination that should be free of charge and facilitate linkage to appropriate care and treatment.